Mediterranean Diet in patients with acute ischemic stroke: Relationships between Mediterranean Diet score, diagnostic subtype, and stroke severity index. Issue 1 (November 2015) - Tuttolomondo, Antonino; Casuccio, Alessandra; Buttà, Carmelo; Pecoraro, Rosaria; Di Raimondo, Domenico; Della Corte, Vittoriano; Arnao, Valentina; Clemente, Giuseppe; Maida, Carlo; Simonetta, Irene; Miceli, Giuseppe; Lucifora, Benedetto; et al.
Abstract: Background: Adherence to a Mediterranean Diet appears to reduce the risk of cardiovascular disease, cancer, Alzheimer's disease, and Parkinson's disease, as well as the risk of death due to cardiovascular disease. No study has addressed the association between diagnostic subtype of stroke and its severity and adherence to a Mediterranean Diet in subjects with acute ischemic stroke. Aim: To evaluate the association between Mediterranean Diet adherence, TOAST subtype, and stroke severity by means of a retrospective study. Methods: The type of acute ischemic stroke was classified according to the TOAST criteria. All patients admitted to our ward with acute ischemic stroke completed a 137-item validated food-frequency questionnaire adapted to the Sicilian population. A scale indicating the degree of adherence to the traditional Mediterranean Diet was used (Me-Di score: range 0–9). Results: 198 subjects with acute ischemic stroke and 100 control subjects without stroke. Stroke subjects had a lower mean Mediterranean Diet score compared to 100 controls without stroke. We observed a significant positive correlation between Me-Di score and SSS score, whereas we observed a negative relationship between Me-Di score and NIHSS and Rankin scores. Subjects with atherosclerotic (LAAS) stroke subtype had a lower mean Me-Di score compared to subjects with other subtypes. Multinomial logistic regression analysis in a simple model showed a negative relationship between MeDi score and LAAS subtype vs. lacunar subtype (and LAAS vs. cardio-embolic subtype). Conclusions: Patients with lower adherence to a Mediterranean Diet are more likely to have an atherosclerotic (LAAS) stroke, a worse clinical presentation of ischemic stroke at admission and a higher Rankin score at discharge. Highlights: Adherence to a Mediterranean Diet appears to reduce the risk of cardiovascular disease. No study has addressed the association between Mediterranean Diet adherence stroke subtype and its severity. Patients with lower adherence to a Mediterranean Diet are more likely to have an atherosclerotic (LAAS) stroke. Patients with lower adherence to a Mediterranean Diet show a worse clinical presentation of ischemic stroke. Patients with lower adherence to a Mediterranean Diet are more likely to have a higher disability at discharge.